The Chad crisis and Operation EUFOR Chad/CAR - Denis Michael Tull (Stiftung Wissenschaft und Politik (SWP), 2008)
Recent fighting between three rebel groups and the Chadian army calls into question the deployment and purpose of Operation EUFOR Chad/CAR, which the Council of the European Union launched on 15 October 2007. The escalation of violence and open French political and military support for the authoritarian regime of President Idriss Déby have fundamentally changed the political circumstances under which the EU operation will be deployed. Therefore, the EU should re-examine EUFOR's underlying purposes. It should also consider abandoning the entire operation
Keywords: 320